Fertility and mineralogy of soils subject to vinasse application on a farm situated in Santa Cruz das Palmeiras-SP, Brazil - Galdeano, Larissa Ruas [UNESP]; Queluz, João Gabriel Thomas [UNESP]; Montibeller, Cibele Carolina [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Garcia, Marcelo Loureiro [UNESP] (UNESP - Universidade Estadual Paulista, 2021)
With the ethanol production expansion in Brazil, there was an increase in the production of vinasse, an effluent from sugar and alcohol industry, which under certain conditions can be used for fertirrigation of sugarcane crops. The research aimed to evaluate the effect of vinasse applied in the period from 2012 to 2017, considering the chemical and mineralogical properties of the soil of a farm located in Santa Cruz das Palmeiras-SP, Brazil. From the results obtained, it was possible to observe that in 2014, which was the year of highest calculation of vinasse dosage, low fertility conditions occurred with high concentrations of H+Al and total CEC. The temporal analysis of one of the farm fields exposed that, in controlled doses, the application of vinasse can improve soil fertility and promote the reduction of acidity and aluminum toxicity. The granulometric and mineralogical tests characterize the studied soil as a sandy soil with high concentrations of silicates and oxides of iron and aluminum. The research evaluated the possibility of leaching of base cations and concentration of H+Al in rainy periods, while moisture and macronutrients would be replaced with fertirrigation in dry periods.
Fertilidade e mineralogia do solo sujeito à disposição de vinhaça de uma fazenda em Santa Cruz das Palmeiras-SP, Brasil
Keywords: Agricultural Engineering; Environment; Pedology